2016
DOI: 10.21693/1933-088x-15.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vascular Disease in Bronchopulmonary Dysplasia

Abstract: Pulmonary vascular disease and pulmonary hypertension (PH) contributes significantly to the pathogenesis, pathophysiology, and clinical course of infants with bronchopulmonary dysplasia (BPD). This article briefly reviews the impact of premature birth on the developing lung circulation, mechanisms that contribute to the development of PH in premature newborns, and the diagnostic evaluation and management of severe PH in infants with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…These findings are consistent with other investigators who have shown impaired cardiac function and fibrosis in adult rodents exposed to neonatal hyperoxia (Bertagnolli et al, ). It should however be noted that the LV dysfunction in our study may be secondary to pulmonary hypertension (Abman, Grenolds, & Mourani, ), as other studies in our lab have demonstrated significantly increased RV systolic pressure in young rats exposed to neonatal hyperoxia (Bryan et al, ). In our present study, we did not evaluate the degree of pulmonary hypertension but we postulate that our current findings of impaired LV function may be secondary to the effects of neonatal O 2 exposure on the systemic vasculature or potentially secondary to pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 46%
“…These findings are consistent with other investigators who have shown impaired cardiac function and fibrosis in adult rodents exposed to neonatal hyperoxia (Bertagnolli et al, ). It should however be noted that the LV dysfunction in our study may be secondary to pulmonary hypertension (Abman, Grenolds, & Mourani, ), as other studies in our lab have demonstrated significantly increased RV systolic pressure in young rats exposed to neonatal hyperoxia (Bryan et al, ). In our present study, we did not evaluate the degree of pulmonary hypertension but we postulate that our current findings of impaired LV function may be secondary to the effects of neonatal O 2 exposure on the systemic vasculature or potentially secondary to pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 46%
“…Taken together, these results suggest that upregulation of these important inflammatory and fibrotic mediators contributes to the induction of BPD pathology by O 2 -EVs in the receipt rats. Although many cell types in the lung could be the targets of circulating EVs, we focused our investigation on PVEC because PVEC would have direct contact with the circulating nanoparticles, and their injury can lead to abnormal vascular development in BPD 37 . Utilizing in vitro PVEC cultures, we demonstrated that O 2 -EVs decreased cell proliferation and increased cell death.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 On the other hand, multiple studies have demonstrated that low DLCO is a predictor of the presence of PH in ILD. 9,31,[37][38][39] Steen and colleagues observed that an FVC:DLCO ratio of >1.4 was an excellent predictor of development of isolated PAH. 40 Seibold reported that an FVC:DLCO ratio of ≥1.8 was a good predictor of death in SSc, while Trad and colleagues found a ratio of ≥2 to predict survival.…”
Section: Diagnosis Screening and Monitoringmentioning
confidence: 99%
“…36 The measurement of the main PA and ascending aorta diameters should be done at the level where the PA bifurcates (when both the right and left PA appear to be of similar size) using electronic calipers. 37 Magnetic Resonance Imaging: Magnetic resonance imaging is more accurate than a computed tomography chest scan. PA diameter and PA-aorta ratio cutoff values >34 mm and >1.1 yielded specificities of 98% and 100%, with corresponding sensitivities of 65% and 50% and positive predictive values of 98% and 100%.…”
Section: Imagingmentioning
confidence: 99%